"I Think It's a Communal Thing": Men's Friendships in Later Life. Issue 1 (January 2014) - Shaw, Rhonda; Gullifer, Judith; Shaw, Rebecca
Men's friendships have traditionally been described as being activity-based but little research has examined older men's friendships. The current study aimed to explore meanings of friendship with older men who belonged to formal men's groups or not. A thematic analysis of focus group data identified three manifest themes ( constructing friendship: friends, mates or acquaintances; the dynamic nature of friendship ; and the importance or beneficence of friendship ) and one latent theme ( community of men ). Friendship was constructed as a multifaceted concept contingent on context. The importance of maintaining friendships were discussed as either self-driven or the responsibility of the other. Talking to like-minded men, regardless of group membership, was valued not just for doing activities but for the emotional support it provided.